Past and future evolution of the onshore-offshore groundwater system of a carbonate archipelago: The case of the Maltese Islands, central Mediterranean Sea - De Biase, Michele; Chidichimo, Francesco; Micallef, Aaron; Cohen, Denis; Gable, Carl; Zwinger, Thomas (Frontiers in Water, 2023)
Offshore freshened groundwater (OFG) is groundwater with a salinity below that of seawater that is stored in sub-seafloor sediments and rocks. OFG has been proposed as an alternative solution to relieve water scarcity in coastal regions and to enhance oil recovery. Although OFG has been documented in most continental margins, we still have a poor understanding of the extent and flow characteristics of OFG systems, and their evolution through time. In view of the general absence of appropriate field data, paleohydrogeological models have been used. The majority of these models are based on 2D approaches, and they rarely consider the future evolution of OFG systems, especially in response to predicted climate change. Here we utilize recently acquired geological, geophysical and hydrogeological data from onshore and offshore the Maltese Islands, and employ 2D and 3D numerical models, to: (i) reconstruct the evolution of the onshore-offshore groundwater system during the last 188 ka, (ii) predict the evolution of the OFG system in response to climate-related changes. We show that the mechanisms emplacing OFG include a combination of active meteoric recharge at present as well as at sea-level lowstands. The Maltese onshore-offshore groundwater system is relatively dynamic, with 23% of groundwater being preserved in the last 18 ka. The control of geology is expressed by the more prevalent distribution of OFG north of the Great Fault, which is associated to the occurrence of low permeability units, and the asymmetry of the groundwater lens during the 18 ka lowstand. A 30% decrease in recharge predicted in the coming 100 years will diminish OFG extent by 38%, whereas sea-level rise will play a negligible role. At present the estimated volume of OFG is 1 km3, which could potentially provide an alternative supply of potable water to the Maltese Islands for 75 years. Exploitation of OFG with minimal salinization of onshore groundwater bodies would require locating pumping wells close to the coast.